Type of exercise may influence postural adaptations in chemotherapy‐induced peripheral neuropathy. Issue 8 (18th July 2021) - Waibel, Sarah; Wehrle, Anja; Müller, Jana; Bertz, Hartmut; Maurer, Christoph
Abstract: Objective: Traditional posturography measurements characterize postural instability in patients with chemotherapy‐induced peripheral neuropathy (CIPN), while underlying postural control mechanisms remain unclear. Taking a model‐based approach can yield insights into these mechanisms. This study's aim was to characterize the modifications in postural control of CIPN patients associated with exercise in relation to the postural behavior of healthy control participants (hCON) via an exploratory approach. Methods: Thirty‐one CIPN patients were randomly assigned to two interventions (balance plus moderate endurance training vs. moderate endurance training only) and exercised twice per week over 12 weeks. Baseline data were compared to 36 matched hCONs. We recorded spontaneous sway and postural reactions to platform tilts using Optotrak and a Kistler force platform pre‐ and post‐intervention. Data interpretation relied on a model‐based parameter identification procedure. Results: Spontaneous sway amplitudes were larger and postural reactions smaller, with a relative phase advance, in our pre‐intervention patients than the hCONs. Post‐intervention, spontaneous sway, and postural reactions were reduced and the sensory‐motor ratio larger in both groups, while the postural reaction timing differed between groups. Interpretation: The abnormally small postural reactions in CIPN patients before the intervention can be interpreted as the consequence of abnormally strong velocity control—a strategy modification that may serve as a prediction mechanism to compensate for the lack of timely and accurate proprioceptive signals. While both groups reduced postural sway and showed an adapted sensory‐motor ratio post‐intervention, the interventions seemed to trigger different velocity control strategies. This study emphasizes the need for taking a more differentiated perspective on intervention effects. Trial registration: German Clinical Trials Register (DRKS) number: DRKS00005419, prospectively registered on November 19, 2013.